What Influences Chinese Consumers’ Adoption of Battery Electric Vehicles? A Preliminary Study Based on Factor Analysis - Wei Wei; Ming Cao; Qianling Jiang; Sheng-Jung Ou; Hong Zou (Energies, 2020)
The rapid development of automobile industry in China did improve people’s quality of life. However, it has also damaged the ecological environment. The emission of a large amount of automobiles is one of the serious air pollution sources. In recent years, the shortage of petrochemical energy, the rapid rise of harmful particles in the air (e.g., PM2.5 and PM10), and the increasing worse atmospheric environment are becoming obstacles to China’s sustainable development. Battery electric vehicles (BEVs) are recognized as an ideal alternative to conventional cars. This study aims to explore the factors that can promote consumers’ adoption of BEVs and to construct domains of these factors. Firstly, an open web questionnaire and semi-structured interviews were conducted to widely collect factors that promote consumers’ purchase of BEVs. Then, questionnaire survey and exploratory factor analysis were used to construct domains of promoting consumers’ purchasing willingness. A total of six factors that promote consumers’ adoption of BEVs were obtained. Finally, the research results can provide references for the Chinese government and the BEV manufacturers in the development and promotion of EVs.